Gender and ethnicity differences in metacognitive skills and problemâ€“solving ability among physics students in johor - Ali, Marlina (2006)
A study on metacognitive skills in relation to problem-solving in physics among secondary school students in Johor, Malaysia is sponsored by Research Management Centre (RMC), UTM under Vot 75161. It has finally completed its data collection and a complete Technical Report is due to be published in January 2007.The study involved a survey on 1300 physics students from nine districts of Johor namely Batu Pahat, Muar, Kota Tinggi, Pontian, Johor Bahru, Segamat, Mersing, Kulai and Kluang. Two well-validated instruments on metacognitive skills and four problem-solving questions on mechanics (Fatin, 2005) were conducted among respondents selected from 9 rural schools and 15 urban schools in Johor using random cluster samplings of form four physics students. The sampling of respondents in this study did not include students from fully residential schools where the â€œcreamâ€ of the Malay students are mostly found. The samples comprised students from daily secondary schools (rural and urban) and premier schools (urban High Schools) in Johor. This paper forms part of the report of the short term research project and focuses only on the development of gender and ethnicity differences on metacognitive and problem-solving skills from three stages of research processes. An indepth literature review related to metacognition and physics problem-solving is discussed fully in Fatin (2005).